Electrochemical Activation of Aluminum by the Addition of Tin, in 3% NaCl - Gouale,Youssef (2019)
The aim of our studies was to show the effect of the addition of tin to aluminum in a solution of sodium chloride (NaCl 3%), by weight, as well as the influence of the alloy immersion time on its corrosion resistance. To do this, we have used, as electrochemical techniques, potentiodynamic polarization and electrochemical impedance spectroscopy and, as metallurgical techniques, hardness parameters and optical microscopy performed on the alloys made of pure aluminum (99.99%) and pure tin (99.99%). The obtained results show that the addition of tin enhances aluminum electrochemical activation, as well as the spontaneous formation of an oxide layer containing Al2O3, which then protects the metal from further corrosion. During all that process, the alloy immersion in 3% NaCl acts by promoting tin's attack and the alloy's corrosion.